UPAYA PENINGKATAN MUTU PEMBELAJARAN MELALUI STANDAR PROSES DI MTsN GIRILOYO IMOGIRI BANTUL TAHUN 2012 (Jurnal Pendidikan Madrasah, 2016)
The purpose of this study was to determine effective measures in improving the quality of learning through Processing Standards in MTsN Giriloyo Imogiri. In all forms of teaching and learning, the learning process is crucial to the success of educational objectives to be achieved. The results showed that, first, teacher is better in term of planning and administration in preparing. Especially the preparation of lesson plan from introduction, core activities and cover. Second, in the implementation of classroom teachers are increasingly targeted, because based lesson plan that has been prepared well. Thirdly, the preliminary activities of the teacher always prepares students both physically and psychologically. Fourth, the practice of learning to do in the classroom on learning core activities are already using exploration, elaboration, and confirmation. Fifth, at the end of the lesson the teacher always gives duty at home, a task both structured and unstructured independent activity, as well as the teacher gives an overview plan future activities.